Spectrum of Congenital Heart Diseases in Eastern Nepal: A tertiary care hospital experience - Shah, Prashant; Sherpa, Kunjang; Pandey, Naveen Kumar; Manandhar, Bhawani; Dhungana, Sahadeb Prasad (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Congenital heart diseases are neglected especially in world’s poorest nations and appear to be ignored and unexplored dimension of health. The exact prevalence and spectrum of congenital heart diseases in Nepal is largely unknown. The aim of this study was to describe the local experience on the magnitude and the pattern of congenital heart disease in order to increase the awareness of the public and health policy makers on its burden in Nepal. Materials & Methods: This is an observational hospital based study carried out in a tertiary care hospital in Eastern Nepal. The duration of this study was from April 2015 to July 2016. The echocardiography reports of all patients clinically suspected of having congenital heart disease were retrieved, and their diagnostic details were extracted. Only patients of day one of life to 14 years of age were included. Congenital heart diseases like bicuspid aortic valve, mitral valve prolapse and various inherited cardiomyopathies were excluded. Results: A total of 330 echocardiograms were performed for clinically suspected congenital heart disease. The mean age of study population was 22.31±34.08 months with male to female ratio of 1.2:1. 23% of clinically suspected congenital heart disease cases turned out to have normal echocardiography. Acyanotic congenital heart disease was most common (81.5%) followed by cyanotic congenital heart disease (14.2%) and obstructive congenital heart disease (4.3%). Atrial septal defect was found to be the most common form of acyanotic congenital heart disease (52%) which was followed by ventricular septal defect (28.8%) and patent ductus arteriosus (14.8%). Tetralogy of Fallot and double outlet right ventricle were the most common form of cyanotic CHD representing 44.4% of all cyanotic patients. Pulmonary stenosis was the most common obstructive congenital heart disease observed in this study population (63.6%). Rarer entities, like d-transposition of great arteries, congenitally corrected transposition of great arteries, various types of total anomalous pulmonary venous drainage, double inlet left ventricle, interrupted aortic arch, Shone complex, etc. were also observed, however represented only the minority of the study population. Conclusion: The spectrum of congenital heart disease seen in this study very likely and only represents the tip of the iceberg. Public awareness programmes and training of health care personnel needs to be emphasized in order to facilitate its early diagnosis and improve its outcome.